2013
DOI: 10.1111/1745-7599.12013
|View full text |Cite
|
Sign up to set email alerts
|

Family nurse practitioner student perception of journal abstract usefulness in clinical decision making: A randomized controlled trial

Abstract: Research abstracts at point of care may be valuable to FNPs if easily accessible and integrated into clinical workflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Other studies found that clinicians who use evidence-based guidelines to make treatment decisions and care plans were more likely to identify health issues in patients using mobile application [ 13 ]. Johnson et al [ 15 ] found that nurse practitioner students perceived the usefulness of the research abstracts for their clinical decision-making using the Web version of PubMed search. Similar to observations of the PubMed4Hh usability testing by shadowing clinicians at the point of care, pilot testing revealed workflow challenges because it did not support our assumption that it would be more convenient to use TBLs compared to use of abstracts at the point of care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies found that clinicians who use evidence-based guidelines to make treatment decisions and care plans were more likely to identify health issues in patients using mobile application [ 13 ]. Johnson et al [ 15 ] found that nurse practitioner students perceived the usefulness of the research abstracts for their clinical decision-making using the Web version of PubMed search. Similar to observations of the PubMed4Hh usability testing by shadowing clinicians at the point of care, pilot testing revealed workflow challenges because it did not support our assumption that it would be more convenient to use TBLs compared to use of abstracts at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this was offered by Dr. Bakken when she stated that, “what clinicians need is decision support tools that fit into their workflow and remind them of evidence-based practice ” [ 13 ]. Nursing scholars also have pointed out that EBP is important to nursing practice to increase confidence in decision making and to improve patient outcomes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations